Dirección y estrategia. Reflexión práctica desde lo humano y lo empresarial - Robles García, Lina Tatiana (Universidad de San Buenaventura - Cali, 2017)
With the present article, the intention is to do a comparison between two essential terms at present of the administrative science: direction and strategy. There is carried out a theoretical description of the concept direction and the elements that it integrate it and the conceptualization of the strategy is identified from different theoretical perspectives and its importance in the origin of the strategic administration. To present the results of the study in the shape of discussion, it is revealed how the strategy affects the efficient functioning of the direction and turns away the proper conception of the term focused in the human being, to lead the attention only to the material results of the strategies and targets of the companies. Nevertheless, like conclusion of this writing, a reflection is carried out about the importance of introducing with major rigidity the human factor in the education of the administration, like subject - matter and main emphasis of the program of study given by the educational institutions.